The new killing fields - Kemp, Darren; BBC Worldwide Ltd. (London : BBC Learning, 2005)
Shows the conflict during the genocide crisis in Sudan.
Copy available in DVD format
Executive producer, Emanuele Pasquall ; reporter, Hilary Anderson
Keywords: Genocide -- Case studies; Genocide -- Sudan -- Case studies; Sudan -- Social conditions